2010
DOI: 10.1007/s00439-009-0779-6
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical fine mapping of the cystic fibrosis modifier locus on 19q13 identifies an association with two elements near the genes CEACAM3 and CEACAM6

Abstract: On 19q13, TGFB1 and the cystic fibrosis modifier 1 locus (CFM1) have been identified as modifiers of the course of the monogenic disease cystic fibrosis (CF). Recently, we have described a transmission disequilibrium at the microsatellite D19S197, localized between TGFB1 and CFM1. To map the corresponding molecular variants, we have selected informative SNP markers within a 600-kb area and compared two-marker-haplotype-distributions between phenotypically contrasting sib pair groups, intending to type only phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Building on our previous experience,18 22 we developed informative microsatellite markers to interrogate these genes (see supplementary material for details). Results of the association study are displayed in figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Building on our previous experience,18 22 we developed informative microsatellite markers to interrogate these genes (see supplementary material for details). Results of the association study are displayed in figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of CF-modifying genes have been investigated by a candidate gene approach as AAT variants have been studied by isoeletric focusing in the early 90 s. 41,42 On the basis of our previous experience, 26,31,33 we have applied a stepwise approach to investigate three candidate genes that have been selected based on transcriptome analysis of intestinal samples for this study. First, we have genotyped at least one highly informative microsatellite in (STAT3 and IFNGR1) or near (IL1B) our gene of interest.…”
Section: Discussionmentioning
confidence: 99%
“…We have compared cases and reference patient populations to detect an association with CF disease severity, CF intrapair discordance and the CFTR-mediated basic defect using as a first-step informative microsatellite markers to interrogate the candidate genes. 26 Here, we describe previously unreported details of: (1) STAT3 where functional data indicate that the intragenic microsatellite used for initial genotyping determines STAT3 expression levels; (2) IL1B where follow-up analysis with intragenic SNPs confirmed the microsatellite signal; and (3) IFNGR1 where haplotype-guided hierarchical fine mapping 33 allowed us to describe the major modifying variants by the base.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, a recent study indicated that CEACAM6 and a regulatory element near the 39 end of CEACAM3 are associated with disease severity in patients with cystic fibrosis [48]. However, a previous study in IBD patients suggested that heterozygous carriers of the DF508 mutation in the CFTR gene, the main susceptibility gene for patients with cystic fibrosis, might exert a protective effect in CD [49], suggesting opposing effects of genetic risk loci for cystic fibrosis and IBD.…”
Section: Discussionmentioning
confidence: 88%